2011
DOI: 10.1007/s12020-011-9451-8
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone induces LHRH and glutamate release through NMDA receptor modulation

Abstract: LHRH release from hypothalamus is influenced by the neurotransmitter glutamate that acts, among others, on NMDA receptors present in LHRH neurons. On the other hand, the neurosteroid allopregnanolone can modulate the activity of specific neurotransmitter receptors and affect neurotransmitter release. We examined the role of allopregnanolone on in vitro LHRH and glutamate release from mediobasal hypothalamus and anterior preoptic area of ovariectomized rats with estrogen and progesterone replacement. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…They observed that GnRH release may be modified by the neurosteroid allopregnanolone, which is synthesized from progesterone. Allopregnanolone stimulates the release of glutamate activating NMDA receptors on GnRH neurons [4]. The results in this work indicate that allopregnanolone strongly stimulates GnRH release.…”
Section: Control Of the Lh Surgementioning
confidence: 73%
“…They observed that GnRH release may be modified by the neurosteroid allopregnanolone, which is synthesized from progesterone. Allopregnanolone stimulates the release of glutamate activating NMDA receptors on GnRH neurons [4]. The results in this work indicate that allopregnanolone strongly stimulates GnRH release.…”
Section: Control Of the Lh Surgementioning
confidence: 73%
“…AKR1C1 can regulate the cellular concentrations of allopregnanolone by preventing its formation from progesterone and by catalyzing allopregnanolone inactivation. Recently it has been shown that allopregnanolone also acts as N -methyl- D -aspartate (NMDA) receptor antagonist in rat [44], modulates NMDA receptor action, and thus induces LHRH release [45]. …”
Section: Human Akr1 Enzymes Implicated In Steroid Metabolismmentioning
confidence: 99%
“…These receptors bind to DNA response elements as homo or heterodimers, recruit co-activators or co-repressors and thus regulate gene transcription [4, 14, 47]. Additionally, AKR1 enzymes also control biosynthesis of neurosteroids and modulate activity of GABA receptor A which act as a ligand-gated ion channel [14, 16, 42] and the ligand-gated and voltage dependent NMDA receptor [44, 45]. …”
Section: Akr1 Enzymes Control Concentrations Of Receptor Ligandsmentioning
confidence: 99%
“…In addition, chronic administration of allopregnanolone contributes to a paradoxical hyperexcitability state by increasing the expression of α4subunit of GABA A receptors (denotes the extrasynaptic receptors insensitive to benzodiazepines) (Smith et al, 2007). The hyperexcitability could be also related to progesterone-induced increase in dendritic spine density with mushroom like spines (Morali et al, 2012), which is similar to estradiol effects (Woolley and McEwen, 1994) and to positive modulation of NMDA receptors and glutamate release (Giuliani et al, 2011). Finally, epileptiform activity causes changes in GABA A receptor subunit composition, which then in turn leads to decreased sensitivity of the GABA A receptors to ligands, including neurosteroids (Joshi et al, 2011).…”
Section: Mechanism-based Differences Between Effects Of Estradiol Andmentioning
confidence: 99%